Pengaruh Big Data Analytics Capability Terhadap Performa Rantai Pasok dan Efek Moderasi Dari Kemitraan: The Effect of Big Data Analytics Capability On Supply Chain Performance and The Moderating Effect of Partnerships - Edward Salim; Erlinda Nusron Yunus (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
This research aims to determine the influence of big data analytics capability (BDAC) on company supply chain performance and whether partnerships between entities in the supply chain moderate this relationship. The ability of Indonesian companies to exploit and analyze big data is increasingly crucial in the Industry 4.0 era. This research uses a survey method, where the population is manufacturing companies in Indonesia, represented by respondents working in the supply chain management scope. The data from 130 companies was analyzed to test the instrument, data distribution, and hypotheses using the linear regression method. The research results show a significant and positive relationship between the human resources and intangibles variables from BDAC on supply chain performance. Still, there is no significant relationship between the tangibles variables from BDAC and supply chain performance. In addition, no moderating effect of supply chain partnerships was found on the relationship between BDAC and supply chains. The research implications will enrich the field of supply chain management, especially regarding the implementation of Industry 4.0 technology, and be a consideration for managers in efforts to improve supply chain performance. Keywords: big data analytics capability, Industry 4.0, manufacture, supply chain partnership, supply chain performance